Developing Recognizing Ability of Hijaiyah Letters Through the Hijaiyah Letter Tree Educational Game Tool at RA Asyarif Sibanggor Jae - Kholilah, Anni; Nur, Kholidah; Mukhlis, Mukhlis (Kepompong Children Centre Journal, 2024)
Educational game tool Hijaiyah Letter Tree is one of the effective and fun games for children. This study aims to determine: 1) how to make an educational game tool, the educational game tool Hijaiyah Tree game, to recognize Hijaiyah Letters for early childhood at RA As Syarif. To determine the effectiveness of the educational game tool, the Hijaiyah Tree Game, for early childhood at RA As Syarif; 2) Use the tool to recognize Hijaiyah Letters for children at RA As Syarif. This study uses the research and development (R & D) ADDIE development model (Analysis-Design-Develop-Implement-Evaluate) developed by Dickand Carey. Data collection in this study using validator questionnaires, observation sheets, interviews, and documentation. The results of this study obtained an average product validation score by media experts of 3.42, adjusted to the scale four convection table in the range of 3.25 < M ≤ 4.00 with the category "good". The assessment by material experts obtained an average product validation of 3.42 adjusted to the scale five convection table in the range of 3.25 < M ≤ 5.00 with the category "Very good". So it can be seen that the overall average is 4.55 from each aspect of the development assessment. It can be concluded that this Hijaiyah Tree educational game tool is declared "Feasible". The children's responses were very positive, showing high enthusiasm for the learning media. The average teacher assessment reached 5.00, which is included in the very good category. Based on the validation and trial results, it can be concluded that the Hijaiyah Letter Tree learning media product is suitable for use and effectively improves children's ability to recognize Hijaiyah Letters. Thus, the Hijaiyah Letter Tree game tool for learning to recognize Hijaiyah Letters is valid and does not need to be revised.